2018
DOI: 10.3892/ol.2018.8412
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic acid prevents the development of interstitial lung disease in a hypochlorous acid‑induced mouse model of scleroderma

Abstract: Interstitial lung disease is the most common complication of systemic sclerosis (SSc) and is associated with a high rate of mortality. Due to the complex pathogenesis of SSc, the therapies currently available remain limited. In the present study, the effect of asiatic acid (AA) on SSc-associated pulmonary fibrosis (PF) and its association with the transforming growth factor-β1 (TGF-β1)/Smad2/3 signaling pathway were evaluated. A hypochlorous acid (HOCl)-induced model of SSc was used to evaluate the therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A growing number of studies have indicated that both exogenous and endogenous ROS participate in the pathogenesis of pulmonary disorders, such as ARDS, COPD, ↑Nrf2 translocation, ↑HO-1, ↓pulmonary vascular remodeling via inhibiting EndMT [87,237,238] ↓pulmonary fibrosis, ↓cyclin D1, ↓cyclin E1, ↓cyclin B1, ↓Bcl-2 protein, ↑p53, ↑p21, ↑cleaved caspase-3 protein [234] repress the adhesion of bacteria [235] ↑SOD, ↑catalase, ↑glutathione peroxidase ↓ type I collagen I, ↓endogenous TGF-β1, ↓α-SMA [236,238] ↓MAPK and NF-κB signaling pathways [40,237] ↓TNF-α, ↓IL-6, ↓IL-1β, ↓MCP-1 [237] Asiatic acid ↓pulmonary fibrosis [241,242] ↓TGF-β1, ↓Collagen I, ↓Collagen III, ↓α-SMA, ↓TIMP-1, ↓NLRP3 inflammasome, ↓Smads and ERK1/2 [242][243][244] ↓ROS, ↓neutrophil elastase (NE) activity, ↓MCP-1, ↓recruitment of inflammatory cells, ↓MAPKs, ↓NF-kB, ↑Nrf2, ↑HO-1, ↑SOD3, ↑catalase [41,243,244] Celastrol ↓NF-κB signaling pathway, ↓NLRP3 activity [245][246] ↓IL-8, ↓TNFα, ↓MCP -1, ↑SOD, ↑catalase, ↓Ednrb/Kng1 signaling pathway [248] ↓MMP 2/9, ↑Nrf2, ↑HO-1, ↑GSTs, ↑NQO1 [88] ↓Bax, ↓caspase-3 [249] Fisetin ↓TNFα, ↓PARP-1 [253] ↓neutrophils and macrophage infiltration, ↓MPO activity, ↓TLR4 expression, ↓NF-κB [254,255] ↑Nrf2, ↑HO-1, ↑glutathione peroxidase-2, ↑reduced glutathione, ↑SOD [89] Galangin ↓TGF-β1-ROS-MAPK pathway, ↓goblet cell hyperplasia, ↓collagen deposition, ↓α-SMA expression, ↓VEGF, ↓MMP-9 [257] ↓IL-4, 5, 13, 17, ↓TNF-α, ↓NO, ↓ROS, ↓EPO, ↓IgE, ↑IFN-γ, ↑PPARγ activity [258] Kaempferol ↓TAK1, ↓NF-κB, ↓MAPK, ↓cytokine production [45,262,264,265] ↓ROS …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies have indicated that both exogenous and endogenous ROS participate in the pathogenesis of pulmonary disorders, such as ARDS, COPD, ↑Nrf2 translocation, ↑HO-1, ↓pulmonary vascular remodeling via inhibiting EndMT [87,237,238] ↓pulmonary fibrosis, ↓cyclin D1, ↓cyclin E1, ↓cyclin B1, ↓Bcl-2 protein, ↑p53, ↑p21, ↑cleaved caspase-3 protein [234] repress the adhesion of bacteria [235] ↑SOD, ↑catalase, ↑glutathione peroxidase ↓ type I collagen I, ↓endogenous TGF-β1, ↓α-SMA [236,238] ↓MAPK and NF-κB signaling pathways [40,237] ↓TNF-α, ↓IL-6, ↓IL-1β, ↓MCP-1 [237] Asiatic acid ↓pulmonary fibrosis [241,242] ↓TGF-β1, ↓Collagen I, ↓Collagen III, ↓α-SMA, ↓TIMP-1, ↓NLRP3 inflammasome, ↓Smads and ERK1/2 [242][243][244] ↓ROS, ↓neutrophil elastase (NE) activity, ↓MCP-1, ↓recruitment of inflammatory cells, ↓MAPKs, ↓NF-kB, ↑Nrf2, ↑HO-1, ↑SOD3, ↑catalase [41,243,244] Celastrol ↓NF-κB signaling pathway, ↓NLRP3 activity [245][246] ↓IL-8, ↓TNFα, ↓MCP -1, ↑SOD, ↑catalase, ↓Ednrb/Kng1 signaling pathway [248] ↓MMP 2/9, ↑Nrf2, ↑HO-1, ↑GSTs, ↑NQO1 [88] ↓Bax, ↓caspase-3 [249] Fisetin ↓TNFα, ↓PARP-1 [253] ↓neutrophils and macrophage infiltration, ↓MPO activity, ↓TLR4 expression, ↓NF-κB [254,255] ↑Nrf2, ↑HO-1, ↑glutathione peroxidase-2, ↑reduced glutathione, ↑SOD [89] Galangin ↓TGF-β1-ROS-MAPK pathway, ↓goblet cell hyperplasia, ↓collagen deposition, ↓α-SMA expression, ↓VEGF, ↓MMP-9 [257] ↓IL-4, 5, 13, 17, ↓TNF-α, ↓NO, ↓ROS, ↓EPO, ↓IgE, ↑IFN-γ, ↑PPARγ activity [258] Kaempferol ↓TAK1, ↓NF-κB, ↓MAPK, ↓cytokine production [45,262,264,265] ↓ROS …”
Section: Discussionmentioning
confidence: 99%
“… 41 Xia et al revealed that AA significantly reduced α‑smooth muscle actin and type I collagen expression by inhibiting ROS generation and the TGF‑β1/Smad2/3 signaling pathway. 243 Jiang et al determined that AA might reduce the levels of MPO, inflammatory cytokines, ROS, and MDA, and may inhibit neutrophil infiltration, while it promotes an increase in SOD and CAT levels 109 by upregulating Nrf2 levels and downregulating NLRP3 inflammasome protein expression in ALI in rats. 244 …”
Section: Chinese Herbal Medicinesmentioning
confidence: 99%
“…In the hypochlorous acid-induced murine model of systemic sclerosis, asiatic acid alleviated pulmonary fibrosis and slowed disease progression compared to untreated mice. Moreover, trans-differentiation of fibroblasts into myofibroblasts was significantly reduced in the lungs of SSc mice treated with asiatic acid [169].…”
Section: Asiatic Acidmentioning
confidence: 97%
“…The NLRP3 inflammasome is activated as a result of the interaction between the intracellular sensor NLRP3 (NOD-, LRR-, and pyrin domain-containing protein 3) and various stimuli and triggers the release of pro-inflammatory cytokines (i.e., IL-1β and IL-18) [ 79 ]; therefore, its inactivation by AA induces anti-inflammatory effects. Pulmonary fibrosis is the most common complication of the autoimmune systemic sclerosis leading to high rates of mortality; the administration of AA in murine models of scleroderma led to the attenuation of the histopathological progression in lungs as well as of the conversion of fibroblasts in muscle fibroblasts [ 80 ]. The underlying mechanisms consisted in the down-regulation of E-selectin and the decrease in the serum levels of anti-DNA topoisomerase-1 autoantibody; in addition, AA normalized the expression of TGF-β1 and the ratio of phosphorylated-Smad2/3/Smad2/3.…”
Section: Asiatic Acidmentioning
confidence: 99%